2019
DOI: 10.3389/fnins.2019.01106
|View full text |Cite
|
Sign up to set email alerts
|

On a Simple General Principle of Brain Organization

Abstract: A possible framework to characterize nervous system dynamics and its organization in conscious and unconscious states is introduced, derived from a high level perspective on the coordinated activity of brain cell ensembles. Some questions are best addressable in a global framework and here we build on past observations about the structure of configurations of brain networks in conscious and unconscious states and about neurophysiological results. Aiming to bind some results together into some sort of coherence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 86 publications
(120 reference statements)
1
22
0
Order By: Relevance
“…One of the possible directions related to brain biophysics may be the study of the energetic basis of the origin and development of thought and language. There are a number of works in this direction, in particular [4,6,[47][48][49][50][51][52][53]. Considering thought as a complex non-equilibrium process, it can be concluded that its development matches the well-known principle of maximum entropy production.…”
Section: Discussionmentioning
confidence: 97%
“…One of the possible directions related to brain biophysics may be the study of the energetic basis of the origin and development of thought and language. There are a number of works in this direction, in particular [4,6,[47][48][49][50][51][52][53]. Considering thought as a complex non-equilibrium process, it can be concluded that its development matches the well-known principle of maximum entropy production.…”
Section: Discussionmentioning
confidence: 97%
“…For example, a recent study showed that enhancing coherence improved memory for older people (Reinhart and Nguyen, 2019). However, too much coherence (very low BEN), such as in the sedation or coma state (Viertiö-Oja et al, 2004;Perez et al, 2019), will make the brain too rigid, unable to form variable brain activity patterns. This situation can happen in the AD continuum because of the escalated compensation demand from the progressive brain function deterioration caused by both aging and AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…As such, unconscious patients regain consciousness when “energy-information coupling” is re-established and coordinated in a coherent spatial and temporal pattern (Kumaz, 2019 ). A recent theory based on thermodynamics indicates that neural networks in a normal brain naturally organize together according to energy costs into a sufficient number of connection “microstates” that lead to consciousness (Perez Velazquez et al, 2019 ). In summary, as the self-organization of neural activity in time and space is coupled and driven by energy flow once energetic homeostasis integrity is disrupted, the impairment of conscious-related information processing across the whole brain will lead to the loss of consciousness.…”
Section: Neuroenergetic Hypothesis Of Consciousnessmentioning
confidence: 99%